Phytochemical Analysis of Selected Medicinal plants of India - Kulkarni, Narendra Anant; Mane, Jayashree (Plantae Scientia, 2019)
The present study has revealed the presence of phytochemicals considered as active medicinal chemical constituents. Important medicinal phytochemicals such as terpenoids, flavonoids, phenols, tannins, steroids, glycosides were studied in the collected samples. Plant Aegle marmelos Corr. having all these phytochemicals. Saponin was found only in two plants out of nine plants i.e. Achyranthes aspera Linn. and Semecarpus anacardium Linn. Terpenoids were found in Aegle marmelos Corr., Calotropis gigantea Linn.R.Br., Mimosa pudica Linn. Terpenoids are reported to have anti-inflammatory, antiviral, antimalarial, inhibition of cholesterol synthesis and antibacterial. Cardiac glycosides content was found in Achyranthes aspera Linn., Aegle marmelos Corr., Mimosa pudica Linn., Tribulus terrestris Linn., Calotropis gigantea Linn.R.Br., Ricinus communis Linn.. Cardiac glycosides have been used for over two centuries as a stimulant in case of cardiac failure. The flavonoids were found in Achyranthes aspera Linn., Aegle marmelos Corr., Calotropis gigantea Linn., Mimosa pudica Linn., Cissus quadrangularis Linn. Mart., Tribulus terrestris Linn. The biological functions of flavonoids apart from its antioxidant properties include protection against allergies, inflammation, free radicals, platelet aggregation, microbes, ulcers, hepotoxins, viruses and tumors.